PENJATUHAN SANKSI PIDANA TERHADAP PENYEBARAN KONTEN VIDEO PORNO MENGENAI PENCABULAN ANAK DI BAWAH UMUR MELALUI CYBER / DUNIA MAYA - Lalu Abi Yu'lla Maulana; Mety Rahmawati (Jurnal Hukum Adigama, 2018)
The unlimited use of Information Technology (IT), has made cybercrime accessible by both adults and minors. Technology can be very useful for daily needs, yet on the other hand, it also can be abused by certain parties including minors (underaged children). The purpose of this study is to examine law enforcement of cybercrime in Indonesia as well as forms of cybercrime that are able to be performed by underaged children. The method  used by the author for this journal is normative legal research method. In this case of cybercrime committed by children under age, law enforcement should involves competent authorities such as psychologists, social supervisor, or other experts so no one makes wrong or bad decision for the children. After the  proccess, parents of children that involved, should be required to closely supervise their children usage of IT.